Perencanaan Sistem Drainase Kawasan Perumahaan Opra City: Drainage System Planning For Opra City Housing Area - Prayogo, Dio Jagat; Nusantara, Danayanti Azmi Dewi (Media Ilmiah Teknik Sipil, 2025)
Opra City Housing, located in Menganti District, Gresik Regency, is a residential area that is vulnerable to waterlogging and flooding, particularly during the rainy season. This condition is mainly caused by high annual rainfall combined with a drainage system that has not been fully integrated or optimized. The study employs both hydrological and hydraulic analyses to provide solutions. Hydrological analysis is carried out to determine the design rainfall and to calculate the runoff discharge using the rational method, while hydraulic analysis is applied to define channel dimensions, the capacity of the retention pond, and the capacity of external drainage channels. Rainfall data were collected from several nearby rainfall stations and processed using the Thiessen polygon method. The design discharge was then calculated based on maximum rainfall intensity and surface runoff coefficients. The study results indicate a right-angled drainage network with a total runoff discharge of 4.517 m³/s. Prefabricated U-ditch sections are used as drainage channels, with the smallest dimensions of 0.3 × 0.2 m for tertiary channels and the largest dimensions of 2 × 1.4 m for primary channels. A retention pond measuring 80 × 80 × 1.5 m with a capacity of 9,600 m³ is also planned. Calculations show that the initial river discharge of 3.374 m³/s at a water level of 0.4 m increases to 7.891 m³/s after receiving runoff, while the river’s maximum capacity of 70.050 m³/s at a water level of 3 m ensures the flow remains safe. Overall, this drainage system is designed to effectively control runoff, reduce flood risk, and minimize environmental impacts on the surrounding area.